A development of high sensitivity magnetic sensor based on giant magnetoresistance with simple implementation on smartphone - Adhi Kusumadjati; Sony Wardoyo; Agung Hirawan; Mochamad Ibnu Alwan; Ramandasoavina Blanchard (International Journal of Applied Mathematics, Sciences, and Technology for National Defense, 2023)
In this paper, the magnetic field-based sensor that can connect with smartphones through Bluetooth connectivity was developed. The design of this high sensitivity magnetic sensor system used Giant Magnetoresistance (GMR) sensors in the form of SOIC8 with AA002-02 series from NVE Corp. The results obtained from the measurements show that the sensor is able to work well when connected to an Android-based smartphone. Measurements were carried out by placing a magnet with a magnetic field strength of 0.4 T in the direction of the sensitivity plane of the GMR sensor. The result showed that the closer the magnet distance relative to the GMR sensor the more voltage signal output from the sensor. Since this developed method is simple but effective for detecting position of magnetic object, the further development of this method will be benefit for many applications.